AFRICAN CHRISTIANITY: A LIVING AND VIBRANT REPOSITORY OF CHRISTIAN FAITH – Part II - Thachuparamban, Johny (Asian Horizons, 2018)
Africa has played a remarkable role in the formation and growth of Christian faith and culture, right from its infancy. The ancient nature of African Christianity has been substantiated in the first part of this article1 which tries to establish African Christianity as one of the pillars of faith in Christendom; a fact corroborated by its unique indigenous spiritual symbols, its traditional proverbs that resonate with Christian wisdom literature, and above all its liturgical innovations and vibrancy both in ancient times and post Vatican Council II. Hence the themes discussed are: African Jesus as an ‘Ancestor par excellence’; African liturgical heritage; the Church as Family of God; African proverbs, and African contribution to world Christianity. All this lends a particular stamp of identity and character to African Christianity, not as a replica of Western or Eastern Christianity, but as a unique and equal tradition, a contemporary repository of Christianity.